2020
DOI: 10.1101/2020.05.01.20088211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of COVID-19 from Chest X-ray images using Deep Convolutional Neural Networks

Abstract: The COVID-19 pandemic continues to have a devastating effect on the health and well-being of the global population. A vital step in the combat towards COVID-19 is a successful screening of contaminated patients, with one of the key screening approaches being radiological imaging using chest radiography. This study aimed to automatically detect COVID-19 pneumonia patients using digital chest x-ray images while maximizing the accuracy in detection using deep convolutional neural networks (DCNN). The dataset cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 34 publications
0
70
0
4
Order By: Relevance
“…They achieved 93.48% for the three-class performance. In comparison to these studies, the ResNet50V2 model in our proposed network (COV-MCNet) showed high accuracy than Ozturk et al [35] and Ioannis et al [37] and comparable accuracy with Asif and Wenhui [36].…”
Section: Performance Metricsmentioning
confidence: 48%
See 1 more Smart Citation
“…They achieved 93.48% for the three-class performance. In comparison to these studies, the ResNet50V2 model in our proposed network (COV-MCNet) showed high accuracy than Ozturk et al [35] and Ioannis et al [37] and comparable accuracy with Asif and Wenhui [36].…”
Section: Performance Metricsmentioning
confidence: 48%
“…DarkNet achieved 87.02% accuracy for 3-class classification. Asif and Wenhui [36] proposed a transfer learning-based deep CNN model Inception V3 architecture to classify COVID-19 pneumonia and the study reported 96% accuracy. Ioannis et al [37] proposed a deep transfer learning-based classification task.…”
Section: Performance Metricsmentioning
confidence: 99%
“…Moreover, some researchers also use an adaptive winner filter for noise reduction [59], Affine Transformation [31] in their research. [2], [5], [6], [8], [10][11], [16], [18], [19], [20], [22], [23] [24],[ [26], [28], [ 30], [32], [37],43], [45], [46], [48], [50], [53], [54], [56], [60], [61], [63], [67] 31…”
Section: Generative Adversarial Network(gan)mentioning
confidence: 99%
“…Flipping or Rotating [1], [2][15], [16], [21], [22], [24], [25], [27], [35], [36], [37], [38], [42], [43], [4 6], [47], [48], [50], [51], [53], [55], [57], [61], [62], [65], [71], [74] 29…”
Section: Generative Adversarial Network(gan)mentioning
confidence: 99%
See 1 more Smart Citation